A Quinta de Santa Efigénia em Setúbal - Ramos, M. (A Magazine, 2023)
The reference to the name of Santa Efigénia on a farm at the entrance to Setlbal deserves a deeper historical study, in the context of the history of the African presence on the peninsula and its political connections and trade with Brazilian lands. As happened in Brazil, in the Sadina region the cult of the saints Eslabaan and Ephigenia would have been instrumental in the process conversion of slave and manumitted populations of African origin.